2014
DOI: 10.1371/journal.pone.0093818
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effects of Flavanol-Rich Lychee Fruit Extract in Rat Hepatocytes

Abstract: Flavanol (flavan-3-ol)-rich lychee fruit extract (FRLFE) is a mixture of oligomerized polyphenols primarily derived from lychee fruit and is rich in flavanol monomers, dimers, and trimers. Supplementation with this functional food has been shown to suppress inflammation and tissue damage caused by high-intensity exercise training. However, it is unclear whether FRLFE has in vitro anti-inflammatory effects, such as suppressing the production of the proinflammatory cytokine tumor necrosis factor α (TNF-α) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 46 publications
3
34
0
1
Order By: Relevance
“…Previous studies indicate that lychee fruit extract contains oligomerized flavanols . Various in vitro and in vivo studies also demonstrated numerous biological activities of lychee fruit extract with oligomerized flavanols, including antioxidant, anticancer, antiviral , anti‐inflammatory , and improving insulin resistance . Dietary lychee fruit extract with oligomerized flavanols reduced adipose mass, adipocyte size, and adipokines secretion as well as hepatic steatosis in high fat diet‐fed mice through modulating multiple molecules such as PPARγ, mammalian target of rapamycin (mTOR)/SREBP‐1 and AMPK signaling .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that lychee fruit extract contains oligomerized flavanols . Various in vitro and in vivo studies also demonstrated numerous biological activities of lychee fruit extract with oligomerized flavanols, including antioxidant, anticancer, antiviral , anti‐inflammatory , and improving insulin resistance . Dietary lychee fruit extract with oligomerized flavanols reduced adipose mass, adipocyte size, and adipokines secretion as well as hepatic steatosis in high fat diet‐fed mice through modulating multiple molecules such as PPARγ, mammalian target of rapamycin (mTOR)/SREBP‐1 and AMPK signaling .…”
Section: Introductionmentioning
confidence: 99%
“…Such oligomerization can result in delivering increased levels of oligomeric proanthocyanidins likely by enhancing bioavailability compared to unoligomerized fruit and plant products [6]. Both in vivo and in vitro studies support the immune regulatory and anti-oxidative effects of Oligonol [813]. Decreased blood levels of IL-6 were reported in healthy humans after 4 weeks of Oligonol administration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both MCP‐1 and IL‐6 gene transcription are mediated by transcription factor, nuclear factor κB (NFκB) . Oligonol inhibited translocation of NFκB from cytosol to nucleus followed by reductions of target gene expression . Oligonol has been reported to inhibit NFκB activation under different pathological conditions including CCl4‐induced liver injury , diabetes‐induced liver and kidney damage , and dextran sulfate sodium‐induced colitis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Oligonol (Amino Up Chemical Co., Sapporo, Japan) was derived from lychee fruit extract and green tea extract. Oligonol contained a polyphenol mixture of flavanols (≥80%) including 13–18% flavanol monomers (catechin, epicatechin, epicatechin gallate, and EGCG), 14–18% dimers (Procyanidin A1, A2, B1, and B2 and epicatechin‐EGCG), 2–6% trimers (Epicatechin‐procyanidin A2), and ≥ 45% other phenolic compounds (other trimers, tetramers, oligomers, and polymers) examined by HPLC . The acute and subchronic toxicity of oligonol has been evaluated by using rats .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation